Prevalence of degree of severity of temporomandibular joint disorder based on sex and age group - Dewanti, Luciana (Padjadjaran Journal of Dentistry, 2009)
Temporomandibular joint disorders are disturbances of mastication system due to one or more component of mastication system does not properly function. The factors that play a role in this problem divided into three factors; a) predisposition factor (systemic, occlusion disturbances and psychological trouble), b) initiation factor (traumatic) and c) perpetuation factor (social behavior). These disorders are able to cause a variety of symptom suck as limitedness of jaw movement, clicking, deviation locked joint, muscle pain, joint pain, jaw movement pain and pain of ear and headache. The objective of this study was to obtain information about the prevalence degree of severity of the temporomandibular joint disorder, the differences of prevalence between man and woman and the different among age groups. The study was descriptive and analysis survey, done to 134 patients as an experimental sample of 3–75-year old that have visited Dental Hospital, Padjadjaran University Bandung, during February 2008. Sample consist of 57 men and 77 women were evaluated by using Helkimo Index and analysis by using Z statistical proportion test to know the existence of difference prevalence degree of severity between man and woman and using the chi-square test to know the difference prevalence among age groups.The result of this study shows that there is highly prevalence severity of temporomandibular joint disorder (84,33%) and significantly different on prevalence severity between man and woman and among a group of ages.The conclusion can be drawn that patients who visited the dental hospital, Padjadjaran University have higher prevalence severity of temporomandibular joint disorder where a woman has higher level compare to man, and the young adult group has highest either man and woman. Clicking is the most often symptom appear to man and woman.